A Decision Model for the Allocation of Foreign Funds to Divident Remittances and Foreign Investment in a Multinational Corporate System with Wholly-Owned Foreign Manufacturing Subsidiaries - Obersteiner, Erich (Journal of Finance, 1973)
Erich Obersteiner, A Decision Model for the Allocation of Foreign Funds to Divident Remittances and Foreign Investment in a Multinational Corporate System with Wholly-Owned Foreign Manufacturing Subsidiaries, The Journal of Finance, Vol. 28, No. 1 (Mar., 1973), pp. 221-222